STUDI TENTANG PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 2 LAMONGAN - INDAH PURNAMAWATI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Education is one sector which is very important in the development of every country. Level of educational success will be seen if the appropriate evaluation tools and can be used to measure each goal. Therefore the form of test evaluation tool used by the teacher in the assessment of student learning outcomes. This study aims to determine the type of evaluation tool used by the teacher and the reason teachers use the evaluation tool, as well as to determine the feasibility of the evaluation tool used by teachers in accounting subjects in class XI IPS SMA Negeri 2 Lamongan. This research is a descriptive study. Techniques of data collection using interviews, and documentation. The results showed that the evaluation tools used in accounting subjects in class XI IPS SMA Negeri 2 Lamongan a written test descriptions, which includes test questions daily and mid-semester test questions. Reasons teachers use the evaluation tool is to determine the progress and setbacks of student learning outcomes. Results of the feasibility study of an evaluation tool to obtain very viable category Keyword: evaluation tool, instrument, test.